2023
DOI: 10.3389/fimmu.2023.1123155
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection impairs NK cell functions via activation of the LLT1-CD161 axis

Abstract: IntroductionNatural killer (NK) cells plays a pivotal role in the control of viral infections, and their function depend on the balance between their activating and inhibitory receptors. The immune dysregulation observed in COVID-19 patients was previously associated with downregulation of NK cell numbers and function, yet the mechanism of inhibition of NK cell functions and the interplay between infected cells and NK cells remain largely unknown. MethodsIn this study we show that SARS-CoV-2 infection of airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…These results suggested that the decrease of CD161 + CD56 + NK cells may contribute to the progression of pSS. Lenart et al found that activation of the LLT1‐CD161 axis can inhibit granzyme B and IFN‐γ production by NK cells and hamper the function of NK cells 29 . CD161 is expressed in the early stage of NK cell development, and in the peripheral circulation, the crosslinking of CD161 leads to upregulate the expression of IFN‐γ and inhibits the cytotoxicity of NK cells 10,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the decrease of CD161 + CD56 + NK cells may contribute to the progression of pSS. Lenart et al found that activation of the LLT1‐CD161 axis can inhibit granzyme B and IFN‐γ production by NK cells and hamper the function of NK cells 29 . CD161 is expressed in the early stage of NK cell development, and in the peripheral circulation, the crosslinking of CD161 leads to upregulate the expression of IFN‐γ and inhibits the cytotoxicity of NK cells 10,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Lenart et al found that activation of the LLT1-CD161 axis can inhibit granzyme B and IFN-γ production by NK cells and hamper the function of NK cells. 29 CD161 is expressed in the early stage of NK cell development, and in the peripheral circulation, the crosslinking of CD161 leads to upregulate the expression of IFN-γ and inhibits the cytotoxicity of NK cells. 10,30 Another study showed that CD161 on NK cells combined with its ligand on target cells and inhibited NK cytotoxicity by activating acidic sphingomyelinase.…”
Section: Laboratory Parameters and Disease Activity Indexmentioning
confidence: 99%
“…In severe COVID patients, NK cells are exhausted due to the induced expression of the inhibitory molecules, including the overexpression of PD-1 on its surface [ 66 , 67 ]. Additionally, SARS-CoV-2 infection impairs NK cell functions by activating the LLT1-CD161 axis, leading to reduced cytotoxicity [ 68 ]. NK cells in COVID-19 patients show dysfunction, characterized by decreased quantity and impaired ability to reduce viral protein levels, similar to tumor-associated NK cells [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…NK cells in COVID-19 patients show dysfunction, characterized by decreased quantity and impaired ability to reduce viral protein levels, similar to tumor-associated NK cells [ 69 ]. NK cells are exhausted and thereby play a negligible role in the acute phase of severe COVID-19 disease in patients [ 20 , 21 , 66 , 67 , 68 , 69 ]. Our results support those clinical findings though further investigation of the exhausted and activated status of NK cells is required.…”
Section: Discussionmentioning
confidence: 99%
“…The virus-induced ongoing inflammation and cytokines may facilitate B-cell proliferation in these patients [ 50 ]. The infected T-cells increase TIGIT and PD-1 expression, possibly leading to a more severe form of COVID-19 [ 92 ]. This negatively impacts the immune system, making way for possible B-cell malignancies.…”
Section: Viral Infectionsmentioning
confidence: 99%